Graphene platelets enhanced pressureless- sintered B4C ceramics. Issue 4 (11th April 2018) - Gao, Dezhi; Jing, Jie; Yu, Jincheng; Guo, Xue; Zhang, Yubai; Gong, Hongyu; Zhang, Yujun
Abstract : B4 C ceramics with different contents of graphene platelets (GPL) were synthesized by a pressureless process in Ar atmosphere. The influences of GPL on mechanical properties, thermal conductivity and electrical resistivity of the B4 C ceramics were investigated. Mechanical properties ran up to optimal condition with hardness of 29.1 GPa, bending strength of 383.9 GPa and fracture toughness of 5.72 MPa m 1/2 with 0.8 wt% GPL separately. Thermal conductivity and electrical resistivity reached extreme values of 26.35 W m −1  k −1 and 0.1 Ω cm −1 . Performances of the ceramics were mainly affected by the generation of non-functional-GPL and the result indicated that a large amount of non-functional-GPL could contribute to poorer overall performance. Meanwhile, two particular pullout mechanisms concerning toughness enhancing was discussed in detail.